2010
DOI: 10.1242/jcs.061358
|View full text |Cite
|
Sign up to set email alerts
|

Splicing-independent recruitment of U1 snRNP to a transcription unit in living cells

Abstract: SummaryNumerous non-coding RNAs are known to be involved in the regulation of gene expression. In this work, we analyzed RNAs that coimmunoprecipitated with human RNA polymerase II from mitotic cell extracts and identified U1 small nuclear RNA (snRNA) as a major species. To investigate a possible splicing-independent recruitment of U1 snRNA to transcription units, we established cell lines having integrated a reporter gene containing a functional intron or a splicing-deficient construction. Recruitment of U sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 71 publications
7
53
0
Order By: Relevance
“…The fact that U2AF65 binds to the phosphorylated CTD, together with earlier observations that U1 snRNP associates tightly with RNAP II in vitro and in vivo, 10,37 indicates that the major factors that recognize the 5' and 3' splice sites at the earliest stage of spliceosome assembly can associate with the RNAP II transcriptional elongation machinery (Fig. 1).…”
Section: Spliceosome Assemblysupporting
confidence: 64%
See 1 more Smart Citation
“…The fact that U2AF65 binds to the phosphorylated CTD, together with earlier observations that U1 snRNP associates tightly with RNAP II in vitro and in vivo, 10,37 indicates that the major factors that recognize the 5' and 3' splice sites at the earliest stage of spliceosome assembly can associate with the RNAP II transcriptional elongation machinery (Fig. 1).…”
Section: Spliceosome Assemblysupporting
confidence: 64%
“…A more recent study examined more directly the dependence of splicing factor recruitment on the presence of a functional intron. Using immunofluorescence, Spiluttini et al 37 showed that U2AF65 recruitment to a transcription unit was reduced if the introns contained mutations that abrogated splicing, in contrast to U1 snRNP, which was still robustly recruited. While this result suggests that the CTD is not sufficient for stable U2AF65 recruitment to transcribed genes, it does not associated with the spliceosome only at a later stage of assembly, where it plays a central role in mediating the conformational changes necessary for splicing catalysis.…”
Section: A U2af65-prp19c Interaction Connects the Ctd With Later Stagmentioning
confidence: 99%
“…In previous work, we found that SR proteins, which associate with U1 snRNP, also must be recruited to premRNA during the RNAP II transcription reaction in order for splicing to occur (19). In addition, we and others found that U1 snRNP/SR proteins are the only essential splicing factors that associate with RNAP II, and this association occurs even when RNAP II is not present at transcription promoters (18)(19)(20). Because U1 snRNP/SR proteins are recruited to pre-mRNA during the earliest steps in the spliceosome assembly pathway (21), the data lead to a model in which U1 snRNP/SR proteins bound to RNAP II are recruited to promoters, and then, while the nascent pre-mRNA is being synthesized, these splicing factors are recruited to the 5′ splice site and adjacent exon to initiate spliceosome assembly.…”
Section: Significancementioning
confidence: 85%
“…In the case of coupled txn/ splicing, studies using the in vitro system revealed that transcription potently enhances spliceosome assembly, which in turn leads to a strong enhancement of the splicing reaction (13). Additional studies revealed that the only essential splicing factors that copurify with RNAP II are U1 small nuclear ribonucleoprotein (snRNP) and its associated factors, the serine/ arginine-rich (SR) proteins (18)(19)(20). This observation is particularly noteworthy because U1 snRNP/SR proteins are the first splicing factors that bind to pre-mRNA during spliceosome assembly (21).…”
mentioning
confidence: 99%
“…The current view is that snRNPs are recruited in a stepwise manner for the formation of the spliceosome on target pre-mRNAs. Recent findings, however, indicate that the recruitment of some snRNPs to nascent transcripts can occur in absence of spliceosomal assembly (Patel et al 2007;Spiluttini et al 2010;Paschedag et al, in revision). This conclusion stems from two main observations.…”
Section: Discussionmentioning
confidence: 99%